Evaluation of various pre-drying treatments for button mushroom qualtiy - Lidhoo, C K; Agarwal, Y C (Mushroom Research, 2011)
Pre-treated slices of button mushroom were dried in hot air (set up at 65Â°C) oven. The dried mushroom was evaluated in different forms by panel of judges and their quality attributes analyzed statistically to determine the effect of pretreatments.Â The two best pre-drying treatments identified were: (a) Blanching in boiling water for 3 min followed by steeping in a solution of 1% KMS + 0.2% CA + 6% sugar + 3% salt at room temperature for 15 min. (b) Blanching in boiling water for 3 min followed by steeping in a solution of 1% KMS +0.2% CA at room temperature for 15 min. It was observed that blanching improved the quality of the dried product. Further the interaction of sugar and salt with chemical preservatives like potassium metabisulphite and citric acid helped in producing better quality product. Sugar and salt when used alone reported low mean scores.Â Also blanched treatments showed longer drying time.